Upaya Meningkatkan Prestasi Siswa Melalui Metode Diskusi pada Mata Pelajaran Aqidah Akhlaq Kelas VIII A di MTs. Sunan Ampel Semanding Pare: UPAYA MENINGKATKAN PRESTASI SISWA MELALUI METODE DISKUSI PADA MATA PELAJARAN AQIDAH AKHLAQ KELAS VIII A DI MTs. SUNAN AMPEL SEMANDING PARE - Lulu' Ali Muchasan (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2015)
The learning method is one of the factors that determine the success of learning. With this method the teacher can convey the subject matter so that it can be understood by students.Among the many methods of learning, discussion is one of the important methods of teaching and learning to be applied in schools, including on subjects Aqidah Morals. With this method, the discussion can be developed courage to express opinions and ideas of students, as well as developing a sense of tolerant and receptive to criticism and opinions of others. The problems are examined to determine the application of the method of discussion in subjects Aqidah Morals in MTs Sunan Ampel Pare- Kediri and the factors that influence it. Based on the research results can be stated that the application of the method of discussion on subjects Aqidah Morals MTs Sunan Ampel Pare Kediri done well, good enough this category demonstrated the application of the teachers in the material that will be discussed in accordance with the learning objectives to be achieved and the implementation of the method used quite smoothly and well. It is powered by a factor of students, factor fasilitas or means, teacher factor, while the inhibiting factor is the limited time available to carry out the discussions, environmental factors.